Reduction in severity of radiation-induced dermatitis in head and neck cancer patients treated with topical aloe vera gel: A randomized multicenter double-blind placebo-controlled trial - Tungkasamit, Tharatorn; Chakrabandhu, Somvilai; Samakgarn, Vatanyu; Kunawongkrit, Natthanan; Jirawatwarakul, Naruemon; Chumachote, Ausareeya; Chitapanarux, Imjai (European journal of oncology nursing : the official journal of European Oncology Nursing Society, 2022)
To assess the efficacy of topical aloe vera gel on radiation induced dermatitis (RID) in head and neck cancer (HNC) patients. In this multicenter randomized double-blind controlled study, HNC patients treated with concurrent chemoradiation (CCRT) received either aloe vera gel or placebo gel. Adverse skin toxicity levels were evaluated with the radiation-induced skin reaction assessment scale (RISRAS). One hundred-twenty patients were enrolled in this study. Analysis of the baseline characteristics did not reveal any differences between the groups. The median RISRAS values from the 1st to the 8th week of the CCRT course were not statistically different between the two groups. In the 5th and 6th weeks of treatment, moderate to severe grades of skin erythematous were observed at values of 13.6% and 24.1% versus 27.8 and 42.6% for members of the aloe vera gel group and the placebo group, respectively (p = 0.05 for the 5th week and p = 0.038 for the 6th week). In the 7th week, moderate to severe instances of moist desquamation were observed in eight patients (19.0%) in the placebo group (p = 0.001). Subjects experienced a burning sensation with RISRAS scores of 3–4 in the 7th week representing only 11.9% of patients in the placebo group (p = 0.016). Topical applications of aloe vera gel significantly reduced moderate to severe grades of skin erythematous and instances of moist desquamation in HNC patients receiving CCRT. In this study, there was no prophylactic efficacy for RID in the aloe vera gel group when compared to the placebo group. •Acute dermatitis is a common side effect in the head and neck cancer patients receiving concurrent chemoradiation.•Standard skin care is recommend from the beginning of the radiotherapy course until the skin has completely recovery.•Aloe vera gel reduced the severity of radiation dermatitis in head and neck cancer patients treated with chemoradiation.